The Road Ahead for Korean Agriculture - 이정환 (한국농촌경제연구원, 2004)
Abstract In the midst of rapid economic growth, the agricultural production structure changed three to seven times faster in Korea than in the cases of many developed countries. As well, the employment structure was also adjusted rapidly to an extent that no other country has ever experienced. As experienced by other countries, the drastic change in the employment structure resulted from a sharp drop in new entrants to agriculture. A major reason is low job mobility among sectors, a common characteristic of labor markets. Accordingly, older farmers have increasingly become the dominant demographic in the sector where more than 50 percent of the agricultural labor force is over 60 years old. Ironically, the current old age-biased structure sheds light on a prospective conclusion that brisk shifts in generations especially for 10 to 20 years, will make the country settle down to the state of developed countries. To achieve a soft landing for this change, it is therefore of extreme importance for Korea to ensure flexible policies for this period in managing or controlling further market openness and reducing domestic support. A number of structural adjustment policies in the 1990s contributed to significant productivity gains by promoting capital accumulation and farmland concentration toward large-sized farms. Expansion of large-sized farms facilitated by the encouragement of farmland leases has been transforming the structural orientation from owner farmers to tenant farmers. A serious concern, however, is raised that gains in farm incomes have not been realized in tandem with the agricultural growth and productivity gains in recent years. Farm household incomes accounted for no more than 75 percent of urban household incomes and a disparity among the incomes of farm households expanded so rapidly that 33 percent of the total farm households suffered from a persistent decrease in incomes in the last five years and the five-tile income ratios increased to 7.1 in 2002. Such a disparity among farm household incomes is largely attributable to many aged farmers with small-scale operations who suffer from declining incomes in nominal terms, facing few opportunities for job change and productivity boosts. The simulated results by a sector-wide forecasting model suggest that direct payments required to compensate for farm income losses amounts to 3.03 billion US dollars in 2010, which exceeds the potential ceiling of domestic support (1.36 billion US dollars) proposed by the Doha Development Agenda negotiations. As developed countries have enjoyed an adjustment to their agricultural problems under border protection and domestic support for a long period, Korea needs some flexibility in the speed of market openness with a view to attain a smooth transformation for its agricultural structure. The Blue Box-type direct payments should be also warranted in at least the short run to accommodate emerging commodity-specific needs for income compensation. This is a parachute for soft landing. It is not fair to take away this parachute which developed countries have used for a long time. This consideration should be relevant to other developing countries. At the same time, the Korean government should ensure market function and continuity of structural adjustment in agriculture as recommended by the OECD. In the context of multifunctional roles of agriculture, the government may consider an integrated approach under which policy measures address agricultural commodities and public goods provided by farming as a whole, given the fact that transaction costs could be prohibitively high.
Keywords: WTO 한국농업